Imaging aspect of neuromyelitis optica: a case report and review of the literature - Lhajoui, H; Bounnit, I; Moussali, N; Merzem, A; Amriss, O; Belgadir, H; Elbenna, N (Archives of Case Reports, 2021)
The case report presents a neuromyelitis optica in a 19 years old male. Brain and spinal cord MRI showed bilateral optic neuropathy, multiphasic demyelinating process involving the cervical and thoracic spinal cord. Cerebrospinal fluid showed negative NMO Ig G. We will describe the radiological aspect of neuromyelitis optica with a review of the literature.